El cultivo legal de adormidera en España: regulación jurídica, características de la empresa concesionaria y naturaleza de la producción (2021)
In this article I analyze the legal production of opium poppy (Papaver somniferum L.) in Spain. First, I review the historical legislation on the subject, characterized by orthodoxy with respect to the international regime and the consequent overlapping between national and international decisions. Subsequently, I describes the cultivation of the narcotic, a strategic product in the tradition of the State monopoly (estanco), and characterize Alcaliber, the concessionaire for decades. Finally, I organize the information from open-source about licenses, hectares and control on the cultivation and harvesting chains, data that was usually scattered due to the legal cultivation of opium poppy.